REKONSTRUKSI BIROKRASI PEMERINTAH DAERAH PENGUJIAN KENDARAAN BERMOTOR BERBASIS NILAI KEADILAN (Study tentang Birokrasi Pengujian Kendaraan Bermotor pada Dinas Perhubungan Kabupaten/Kota di Jawa Tengah) - Imam Sudrajat (UNISSULA, 2014)
Implementation of Bureaucracy in testing at the Motor Vehicle Department of Transportation District/town in Central Java is not based on the value of justice due to the Problem Statement that occur in relation to services and feasibility testing of motor vehicles is not only a service procedure, but the commitment of employees to carry out services and feasibility testing of motor vehicles less reflect fairness and transfaransi. Servicing and testing the feasibility of a motor vehicle cannot fully satisfy the community because people's understanding of the feasibility of testing services of motor vehicles, apparently not all of them know and understand procedurally. To perform reconstruction Bureaucracy, used Progressive Legal Theory equitable, with steps taken by the privatization Motor Vehicle Inspection, Supervision improve the effectiveness, efficiency and transfer of oil fuel sources, restrictions on vehicle age and vehicle progressive taxation.